MAINSTREAMING JURNAL ILMIAH SEBAGAI PLATFORM PENGEMBANGAN KURIKULUM MANAJEMEN DAKWAH (Studi di Prodi Manajemen Dakwah UIN Sunan Kalijaga) - M. Rosyid Ridla; Bayu Mitra A. Kusuma; Munif Solikhan (Jurnal MD, 2017)
Da’wah activities are required to always adjust to the development and the needs of era, so dakwah can no longer be described just as doctrinal studes, but rather the strategy for bringing ummah to transform socially. Therefore, as part of Tri Dharma, universities should build a strong and adaptive curriculum to produce competent alumni in their fields. One of the strategies that need to be put forward is through mainstreaming scientific journals because today's publications are becoming vital points in assessing academic productivity, measuring the depth of a person's social analysis, or maintaining the credibility of an institution. To address this matter, Faculty of Da’wah and Communication UIN Sunan Kalijaga made a breakthrough by establishing a journals house at the faculty level. The effort is supported by the Department of Da'wah Management through several strategic steps such as: implementation of cultural and structural strategy through Jurnal MD, encouraging academic community to productively writing in accordance with their field and interest of the study, pouring lecturer and student activity into manuscript deserve to be published, and organize academic forums to obtain quality manuscript.